Thermoluminescent characterization of Al2O3-derived synthetic topaz - Trujillo Vazquez, E. (2016)
Albeit the thermoluminescent properties of both Al2O3 and natural topaz have been documented, owing to a controlled composition, the prospective of synthetic topaz for dosimetry applications is expected to be further promising. In this contribution, the thermoluminescent (Tl) properties of synthetic topaz (Al2F1.44(OH)0.56SiO4) containing materials are reported for the first time. Synthesis tests by chemical vapor deposition (CVD) were conducted using aluminum oxide (Al2O3) and sodium hexafluorosilicate (Na2SiF6) as solid precursor, varying temperature, time, Al2O3 compact angle position, and atmosphere during dwell stage (with and without nitrogen). Subsequently, samples were thermally treated at 500, 600, 700, 750, 800, 850 and 900 °C. Results indicate that samples treated at 800 °C show a standard deviation of 1.2% (SD %) of the area under the glow curve in the range 53–300 °C. Irradiation with 90Sr beta-source of sample A4 (800 °C), from 0.022 Gy to 66 Gy, revealed a nonlinear response, with intensity increasing as doses increase. In addition to the fact that synthesized topaz-containing material possesses a similar Tl intensity compared with that of the commercial dosimeter TLD-100, incidence of the greatest fading (<22%) during the first 20 h suggests its potential application in dosimetry.